Correction: The dual-defect passivation role of lithium bromide doping in reducing the nonradiative loss in CsPbX3 (X = Br and I) quantum dots. Issue 2 (23rd December 2020) - Wu, Hao; Qiu, Jianbei; Wang, Jing; Wen, Yugeng; Wang, Qi; Long, Zhangwen; Zhou, Dacheng; Yang, Yong; Wang, Dazhao
Abstract : Correction for 'The dual-defect passivation role of lithium bromide doping in reducing the nonradiative loss in CsPbX3 (X = Br and I) quantum dots' by Hao Wu et al., Inorg. Chem. Front., 2020, DOI: ; 10.1039/d0qi01262a .